2018
DOI: 10.3390/ijms19082451
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Pharmacology of Palladinum(III) Hematoporphyrin IX Complexes: Solution Stability, Antineoplastic and Apoptogenic Activity, DNA Binding, and Processing of DNA-Adducts

Abstract: Two paramagnetic PdIII complexes of hematoporphyrin IX ((7,12-bis(1-hydroxyethyl)-3,8,13,17-tetramethyl-21H-23H-porphyn-2,18-dipropionic acid), Hp), namely a dinuclear one [PdIII2(Hp-3H)Cl3(H2O)5]·2PdCl2, Pd1 and a mononuclear metalloporphyrin type [PdIII(Hp-2H)Cl(H2O)]·H2O, Pd2 have been synthesized reproducibly and isolated as neutral compounds at different reaction conditions. Their structure and solution stability have been assayed by UV/Vis and EPR spectroscopy. The compounds researched have shown in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…In the past few decades, the platinum-containing cisplatin and its corresponding carboplatin and oxaliplatin analogous were considered to be the most innovative anticancer drugs . And the cisplatin platinum-based drugs have been first widely used as chemotherapeutic drugs for the treatments of different human tumors, such as head, neck, lung, ovarian, testicular, and bladder cancers .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past few decades, the platinum-containing cisplatin and its corresponding carboplatin and oxaliplatin analogous were considered to be the most innovative anticancer drugs . And the cisplatin platinum-based drugs have been first widely used as chemotherapeutic drugs for the treatments of different human tumors, such as head, neck, lung, ovarian, testicular, and bladder cancers .…”
Section: Introductionmentioning
confidence: 99%
“…9 In the past few decades, the platinum-containing cisplatin and its corresponding carboplatin and oxaliplatin analogous were considered to be the most innovative anticancer drugs. 10 And the cisplatin platinum-based drugs have been first widely used as chemotherapeutic drugs for the treatments of different human tumors, such as head, neck, lung, ovarian, testicular, and bladder cancers. 11 The resistance of platinum-based drugs in cancer cells might be caused by various mechanisms such as the counteract of platinum toxicity, a rise in drug export from the cell, and the barrier of platinum-based drugs into the nucleus of the cell, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Recent developments in antitumor coordination compounds (Momekov and Momekova 2006;Shaili 2014) is synthesis of cytotoxic platinum, palladium and gold metal complexes with porphyrin ligands (Doneva et al 2014), as hematoporphyrin IX complexes: monomeric platinum (III) (Momekov et al 2010), paramagnetic platinum (Gencheva et al 2007), palladium III (Momekov et al 2018), andgold II complexes (Momekov et al 2008); platinum complexes with an alternative DNA-binding and tumor-targeted cytotoxicity (Momekov et al 2005); platinum (IV) agents: Enthacraplatin, Iproplatin, Mitaplatin, Ormaplatin (Tetraplatin), Satraplatin (Monneret 2011). (Meng et al 2013), testicles (Dhar et al 2011), esophagus (Koizumi et al 2008), stomach, colon, pancreas, liver, kidney, prostate (Desoize and Madoulet 2002), bladder (Dasari and Tchounwou 2014), breast (Decatris et al 2004), small cell lung, non-small cell lung (Minami et al 2013), gastric (Koizumi et al 2008) cancers, malignant brain glioblastoma, head and neck squamous cell carcinoma, refractory non-Hodgkin's lymphoma and sarcoma (Dasari and Tchounwou 2014), peritoneal and pleural mesothelioma, neuroblastoma, metastatic melanoma, leukemia (Previati et al 2006) Carboplatin ovarian, cervical, testicular, brain, bladder, breast, head, neck (Hong et al 1996), small cell lung cancer (Hong et al 1995;Zang et al1999) Lobaplatin chronic myelocytic leukemia, small-cell lung, breast, gastric cancer, esophageal squamous cell and hypopharyngeal carcinoma, osteosarcoma (Gienema et al1993;Degardin et al 1995;Wu et (Yao et al 2007;Pabla and Dong 2008;Miller et al 2010), ototoxicity (Waissbluth and Daniel 2013), myelosuppression (Oun et al 2018) Carboplatin neuropathy, nephro-, otoand gastrointestinal...…”
Section: Introductionmentioning
confidence: 99%
“…Yu-Wen Chen et al showed that the i-motif DNA sequence may transition to a base-extruded duplex structure with a GGCC tetranucleotide tract when it is bound to the (Co II )-mediated dimer of chromomycin A3 [1]. G. Momekov et al investigated two paramagnetic palladium(III) complexes of hematoporphyrin IX for their ability to process DNA adducts as well as for their antineoplastic and apoptogenic activities [2]. E. Makkonen et al reported a combined quantum mechanics/molecular mechanics molecular dynamics and time-dependent density functional study of silver-mediated deoxyribonucleic acid nanostructures [3].…”
mentioning
confidence: 99%